5
$\begingroup$

I know that the derivative of the inverse function of $f(x)$ is $g'(y) = \frac{1}{f'(x)}$ But how to derive the formula for the second derivative of g(y) knowing that $\left[\frac{1}{f(x)}\right]' = -\frac{f'(x)}{(f(x))^2}$ ?

I just started studying this chapter, so please try to be as simple as possible ;-) Thank you.

$\endgroup$
9
$\begingroup$

It is $$g(f(x)) = x \Longrightarrow g'(f(x))\cdot f'(x) = 1 \Longrightarrow g''(f(x))\cdot f'(x)^2+g'(f(x))\cdot f''(x) = 0 \Longrightarrow g''(y) = -\frac{f''(x)}{f'(x)^3}$$

$\endgroup$
  • $\begingroup$ thank you! it was really that simple! Just a single question: if f(x) = g(x), can I also precisely say that f'(x) = g'(x)? Because you used this property at the second implication... $\endgroup$ – Umar Jamil Dec 2 '12 at 16:30
  • $\begingroup$ Yes .. if you have two identical functions they have the same derivation. I used this fact twice (for the first implication and for the second implication also) $\endgroup$ – user127.0.0.1 Dec 2 '12 at 18:49
1
$\begingroup$

Note that $y = f(x)$ and $x = g(y)$ in the formula $g'(y) = \frac{1}{f'(x)}$. Hence you can now write $$ g'(y) = \frac{1}{f'(g(y))} \, . $$ Now use the chain rule and the known formula for $g'(y)$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.